Research on Climate Change Policies and Rural Development in Latin America: Scope and Gaps - Locatelli, Bruno; Aldunce, Paulina; Fallot, Abigail; Le Coq, Jean-François; Sabourin, Eric; Tapasco, Jeimar (MDPI, 2017)
Research on climate change policies can contribute to policy development by building an understanding of the barriers faced in policy processes, and by providing knowledge needed throughout policy cycles. This paper explores the thematic coverage of research on climate change policies related to rural areas, rural development, and natural resource management in Latin America. A three-tier framework is proposed to analyse the selected literature. The results show that research studies have focussed on the mitigation of greenhouse gas emissions from forests, and adaptations to climate change in agriculture. There is little policy research on other vulnerable sectors (e.g., water and health) and emitting sectors (e.g., energy and industry) in the context of rural development. Our analysis highlights the various research gaps that deserve increased scientific attention, including: cross-sector approaches, multi-level governance, and the stages of policy adoption, implementation and evaluation. In addition, the selected literature has a limited contribution to theoretical discussions in policy sciences.